Investors Facing Risk: Loss Aversion and Wealth Allocation Between Risky and Risk-Free Assets - Erick W. Rengifo; Emanuela Trifan (Technische Universität Darmstadt, Department of Law and Economics, 2006)
This paper studies the impact of loss aversion on decisions regarding the allocation of wealth between risky and risk-free assets. We use a Value-at-Risk portfolio model with endogenous desired risk levels that are individually determined in an extended prospect theory framework. This framework allows for the distinction between gains and losses with respect to a subjective reference point as in the original prospect theory, but also for the influence of past performance on the current perception of the risky portfolio value. We show how the portfolio evaluation frequency impacts investor decisions and attitudes when facing financial losses and analyze the role of past gains and losses in the current wealth allocation. The perceived portfolio value exhibits distinct evolutions in two frequency segments delimitated by what we consider to be the optimal evaluation horizon of one year. Our empirical results suggest that previous research relying on VaR underestimates the aversion of real individual investors to financial losses.
Keywords: C32; C35; G10; 330; prospect theory; loss aversion; capital allocation; Value-at-Risk; portfolio evaluation